LITERARY EXPRESSION OF HUMAN AND MYSTICAL PERFECTION IN SOHRAB SEPEHRI’S POETRY - Shoaliyeva Nargiza (International Journal of Innovative Technologies in Social Science, 2019)
In the poem “Address”, which was included in the collection “Green Volume” by S.Sepehri, in his own way he interprets the seven stages of asceticism - the “seven valleys”, which are given in the dastan of Sheikh Fariduddin Attar “Mantik ut-tyr” (“Journey of Logic”). The article provides a comparative analysis of the spiritual stages of the poet's poetry - talab (need), ishq (love), marifat (enlightenment), isthiqno (denial), tavhid (unity), zairat (shock), fair (poverty) faqr fano (eternity). The path of Sufi perfection in the poem "Adress" is interpreted by the poet as a search for a "friend's house." In "The Journey of Logic," the path through the seven valleys ends in the valley of "poverty and eternity." Unlike Attar, Sepehri's path to perfection does not end at the "eternity" stage. It develops cyclically. Each time, without reaching the end, the path to the truth begins anew in a new form.